(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Urolithiasis is a widespread urological disease that tends to increase in prevalence worldwide (Lee et al. 2021). Kidney stones are formed from a variety of minerals and salts, including calcium, oxalates, and uric acid, and can range in size from tiny particles to large stones that can cause urinary tract obstruction. The main pathophysiological cause of the formation of urinary stones is an oversaturation of urine salts (Moussa, Papatsoris, and Chakra 2021). Kidney and ureter stones are a serious health problem, as if left untreated, they can cause severe pain, urinary tract infections, and kidney damage even to the point of complete shriveling. There are non-invasive and invasive treatments for kidney and ureter stones. Options for non-invasive treatment of kidney and ureteral stones include medication and extracorporeal shock wave lithotripsy.